Approaches for the Interpretation of Multiple Discriminant Analysis in Organizational Research - Watson, Collin J. (Academy of Management Review, 1982)
The use of plots of multiple discriminant analysis (MDA) results and the use of discriminant function rotations to improve interpretability of findings in organizational research applying MDA are examined and illustrated. A simple, innovative plotting procedure, which depicts overlaps of groups in MDA combined with the traditional depiction of differences among groups, is discussed and illustrated. An example taken from a health care administrative application is presented for illustrative purposes.